Estudio de factibilidad para la creación de un centro clínico, especializado en hemodiálisis, cantón El Empalme, Año 2014. - Zambrano Peralta, José Geovanny (2015)
In recent years, it has been observed that in the world has been growing at an alarming finding hemodialysis services for the benefit of people with kidney problems, which has led many countries to opt for the implementation of centers to solve this social problem, taking into account that in the Canton Junction is an urgent need to have a dialysis center project in its various sections dealing is done: The chapter establishes the contextual framework of the investigation, a diagnosis of the current situation of the problem is done, raised the objectives, assumptions, and research is warranted. Chapter two covers the theoretical framework, where Theoretical, Conceptual and Legal Foundations detailed. In chapter three methods, types, investigative techniques, besides the reference population is determined and the sample size are identified In chapter four the results achieved by conducting a market survey, which allowed the identification and quantification of supply and demand, presented the technical study, which seeks to determine the optimal size, location, machinery and equipment for the operating process dialysis center; then the economic feasibility is….